3D Food Printing - Paesano, Antonio (Handbook of Sustainable Polymers for Additive Manufacturing, 2022)
This chapter reviews the feedstocks, processes, applications, benefits, limitations, and market of 3D food printing (3DFP). The range of foods compatible with 3DFP is broad, and includes members of all major food groups: added sugars, dairy, fruits, grains, vegetables, oils, protein food (meats, poultry, seafood, etc.), and solid fats. The ingredients are processed in form of gel, filament, liquid, paste, and powder. Examples of commercial and experimental foods 3D printed are included along with the relative technical literature. 3DFP is mostly performed through binder jetting, extrusion, material jetting, and powder bed fusion, and these processes and their relative feedstocks and published research are elucidated. The properties of food suited for 3DFP are discussed in order to provide guidelines to formulators of food for 3DFP and printer manufacturers. The status and market of 3DFP currently and in the near future, companies and research institutions involved, patents, commercial printers, and challenges to its diffusion are illustrated. Recent technical literature and comprehensive reviews published on the subject are cited.